Sustainable cities versus political context: where do we go? the case of Radio Base Stations (RBS) of Porto Alegre/RS - Schiavi, Cristiano Sordi; Pedrozo, Eugenio Avila (Revista de Administração da UFSM, 2020)
This article aims to analyze the participation of social actors in the decision-making and political processes of the city of Porto Alegre, concerning the installation of Radio Base Stations (RBSs). Thus, an exploratory and descriptive research of qualitative nature was performed choosing the case of Porto Alegre. As a result, there was an environmental retreat in community participation and a change of orientation in the discussion about the possible adverse effects caused by electromagnetic of RBS. In a period of little more than a decade, the initial protagonism of the community was reduced, when a new discussion about changes in the Law emerged in 2013 and 2014. Finally, the article reinforces the importance of the political decentralization for Sustainable Development of cities, favoring the participation of local actors in the construction of environmental public policies.